MiR‐20b, miR‐296, and Let‐7f Expression in Human Adipose Tissue is Related to Obesity and Type 2 Diabetes. Issue 2 (30th December 2018) - Gentile, Adriana‐Mariel; Lhamyani, Said; Coín‐Aragüez, Leticia; Clemente‐Postigo, Mercedes; Oliva Olivera, Wilfredo; Romero‐Zerbo, Silvana‐Yanina; García‐Serrano, Sara; García‐Escobar, Eva; Zayed, Hatem; Doblado, Esther; Bermúdez‐Silva, Francisco‐Javier; Murri, Mora; et al.
Abstract : Objective: This study aimed to analyze the potential association of different microRNA (miRNA) molecules with both type 2 diabetes (T2D) and obesity and determine their target genes. Methods: Quantitative PCR was used to analyze the miR‐20b, miR‐296, and Let‐7f levels in human visceral and subcutaneous adipose tissues (ATs) in relation to obesity and T2D, miRTarBase 4.0 was used for validation of target genes, and the Protein Analysis Through Evolutionary Relationships (PANTHER) Classification System and the Database for Annotation, Visualization and Integrated Discovery (DAVID) were used to annotate the biological processes of the predicted targets. Results: In AT, miR‐20b, miR‐296, and Let‐7f levels were significantly different between normoglycemic subjects and those with T2D. In visceral adipose tissue, miRNA levels were higher in normoglycemic/obesity samples than in T2D/obesity samples. miR‐20b‐miR‐296 and Let‐7f target genes that showed significant differences in both ATs in relation to obesity and T2D were CDKN1A, CX3CL1, HIF1A, PPP2R1B, STAT3, and VEGFA. These genes are known to be principally involved in the vascular endothelial growth factor (VEGF) and WNT pathways. Conclusions: This study provides experimental evidence of the possible correlation between AT miR‐20b‐miR‐296‐Let‐7f with obesity and T2D, which might involve vascular endothelial growth factor and WNT‐dependent pathways that are regulated by six different genes, suggesting a novel signaling pathway that could be important for understanding the mechanisms underlying the AT dysfunction associated with obesity and T2D.